The Effect of Planting Time and Plant Density on Radiation Use Efficiency (RUE) on Lowland Rice (Oryza sativa L.) Cv. Inpari 30 - Diyoprakuso, First; Suryanto, Agus; Soelistyono, Roedy (Kadiri University - Faculty of Agriculture, 2022)
The right planting time and plant density in rice cultivation in the rainy season affect the generative phase, where absorption of solar radiation intensity more efficiently increases productivity. This study aims to improve the absorption of energy efficiency of solar conversion with differences in planting time and planting density. The experiment was carried out from January to June 2019 in the experimental garden of Brawijaya University, Malang City, East Java. The research design used is a nested design with three replication. The main factor is planting time which consists of 3 levels, namely: January (B1); February (B2); March (B3). The nested factor is plant density which consists of 3 levels, namely: 111.111 plant ha-1 (T1); 166.667 plant ha-1 (T2); 226,667 plant ha-1 (T3). Data analysis used variance (ANOVA). If the results are significantly different, then the honest significant difference test (HSD) is continued at the 5% level. The results showed the differences in total leaf area index, plant dry weight, panicle weight every clump, grain weight every clump, grain weight every harvest plot, yield per hectare, and radiation use efficiency (RUE). The planting time in March has a higher RUE value than the planting time in January or February. The yield per hectare shows the planting time in March is higher than the planting time in January or February planting time. Plant density of 30x30 cm shows yields per hectare higher than planting density of 30x20 cm and planting density of 40x20x12.5 cm.Â